How i read cancer imaging studies: the master class series. Issue 1 (December 2016) - Hicks, Rodney
Abstract The generation of a report of findings and a conclusion for an imaging study is a fundamental process in the diagnostic work-up of cancer patients and plays a critical role in treatment decisions. It is therefore important that cancer imaging specialists understand the needs of referring clinicians and can perform this process in a methodical manner. Surprisingly, in contrast to the literature regarding the outcomes of imaging, education regarding the methods that underpin the generation of a report and how to communicate the findings cogently to referring clinicians is rather sparse. In an upcoming series of articles that will appear in inCancer Imaging, experts in various modalities will detail their approach to reporting scans in particular disease settings. In this article some personal perspectives on the process of reporting scans will be detailed as a guide to what will be elaborated in the "Master Class Series".